ANALISIS FAKTOR DETERMINAN KEJADIAN WASTING PADA BALITA DI WILAYAH KERJA PUSKESMAS PAAL V KOTA JAMBI - Annisa Risqi Amelia; Fadliyana Ekawaty; Yuliana (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Wasting is a form of acute malnutrition among children under five characterized by a weight-for-height index below the established standard. This condition increases the risk of growth impairment, susceptibility to infectious diseases, and mortality. Given its multifactorial nature, identifying the determinants of wasting is essential for developing effective prevention and intervention strategies. This study aimed to analyze the determinants of wasting among children under five in the working area of Paal V Public Health Center, Jambi City. An analytical observational study with a case-control design was conducted involving 66 children under five, consisting of 33 cases and 33 controls selected through purposive sampling. Data were analyzed using the Chi-square test and binary logistic regression. The results revealed significant associations between dietary intake (p = 0.007; OR = 4.025), infectious diseases (p = 0.020; OR = 3.496), history of exclusive breastfeeding (p = 0.048; OR = 2.714), immunization status (p = 0.024; OR = 3.200), maternal knowledge level (p = 0.041; OR = 2.941), and the incidence of wasting. Conversely, no significant associations were found between gender, environmental sanitation, maternal occupation, family income, and wasting incidence. Multivariate analysis identified dietary intake as the most dominant determinant of wasting (p = 0.021; AOR = 0.249; 95% CI = 0.076–0.812). In conclusion, dietary intake is the primary determinant of wasting among children under five in the working area of Paal V Public Health Center, Jambi City. Therefore, efforts to prevent and reduce wasting should prioritize improving children's nutritional intake while strengthening maternal knowledge regarding child nutrition and health.